2011
DOI: 10.1111/j.1742-7843.2011.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Decreases Plasma Levels of Osteoprotegerin in a Randomized Clinical Trial with Type 2 Diabetes Patients

Abstract: Cardiovascular disease is the leading cause of death in patients with type 2 diabetes mellitus (T2DM). We suggested that plasma osteoprotegerin (OPG), a strong, independent predictor of cardiovascular disease, could discriminate between anti-diabetic treatments depending on their benefits regarding cardiovascular disease. The South Danish Diabetes Study, an investigator-driven, randomized, controlled clinical trial lasting 2 years, was used to test this hypothesis in patient groups with different medication st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
3
14
1
Order By: Relevance
“…In line with our findings, recently a pilot study in PCOS found comparable levels of OPG in PCOS women and their age-and BMI-matched controls to remain unaffected during insulin sensitizing treatment with pioglitazone [39]. To the best of our knowledge, only two studies have assessed the efficacy of metformin and pioglitazone/rosiglitazone treatment on the levels of OPG in T2DM subject, with both of these reports demonstrating a significant reduction in OPG only with pioglitazone/rosiglitazone treatment [40,41]. In this regard, more studies on the comparative effect of pioglitazone and metformin with lengthier follow-ups are needed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, recently a pilot study in PCOS found comparable levels of OPG in PCOS women and their age-and BMI-matched controls to remain unaffected during insulin sensitizing treatment with pioglitazone [39]. To the best of our knowledge, only two studies have assessed the efficacy of metformin and pioglitazone/rosiglitazone treatment on the levels of OPG in T2DM subject, with both of these reports demonstrating a significant reduction in OPG only with pioglitazone/rosiglitazone treatment [40,41]. In this regard, more studies on the comparative effect of pioglitazone and metformin with lengthier follow-ups are needed.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports in T2DM-induced atherosclerosis demonstrated plasma OPG levels are positively correlated with FPG and HbA1c [41,46], however, in our series of newly diagnosed T2DM subjects; we found no significant relationship between theses indices and OPG serum levels. Similarly, Nybo et al found that the OPG reducing effect of rosiglitazone in T2DM subjects is not seen with metformin despite similar reductions in HbA1c [40]. In line with our findings, Secchiero et al suggested that the inflammation-driven hyperglycemia, rather than the high glucose levels per se, is involved in the increase of OPG observed in both diabetic patients and diabetic mice [10].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings fit well with the notion that metformin may exert direct beneficial effects in the arterial wall and expand this idea by pointing toward metformininduced alterations in the metabolism of the ECM molecule fibulin-1. Somewhat surprising, we did not find that rosiglitazone changed plasma fibulin-1, despite the fact that previous publications have shown that glitazones may influence arterial functions and change vascular biomarkers (41,42). Nevertheless, it seems that even though rosiglitazone may reverse endothelial dysfunction, it did not change arterial remodeling in a study of Zucker diabetic fatty rats (43).…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, Lrp5 can regulate the osteoblast-osteoclast coupling by affecting the RANK-RANKL and OPG pathways (30). Compared with rosiglitazone, which is also a diabetes drug, metformin maintains the plasma levels of OPG and rosiglitazone decreases the plasma levels of OPG in patients with type 2 diabetes (31). Metformin was recently shown to reduce osteoclast differentiation and activity by stimulating OPG and inhibiting RANKL mRNA and protein expression in osteoblasts (11).…”
Section: Discussionmentioning
confidence: 98%